Business Regulations and Growth - Divanbeigi, Raian (World Bank, Washington, DC, 2015)
Over the past decade, there has been increased interest in improving business regulations, in part because of the increased availability of data that can inform and monitor those improvements. This paper analyzes whether these regulatory changes are linked to economic outcomes. With panel data for 10 years across more than 180 countries, the paper establishes the link between business regulations, firm creation, and growth. It is found that an improvement of 10 points in the overall measure of business regulations is linked to an increase of around 0.5 new businesses per 1,000 adults. Moreover, the results show that although small changes in the overall level of business regulations may have a negligible link to growth, moving from the lowest quartile of improvement in business regulations to the highest quartile is associated with a significant increase in annual per capita growth of around 0.8 percentage points. In addition, the results highlight the importance of sound entry and exit regulations and sound credit market regulations and court enforcement for growth.